BHRF1, a BCL2 viral homolog, disturbs mitochondrial dynamics and stimulates mitophagy to dampen type I IFN induction. Issue 6 (3rd June 2021) - Vilmen, Géraldine; Glon, Damien; Siracusano, Gabriel; Lussignol, Marion; Shao, Zhouwulin; Hernandez, Eva; Perdiz, Daniel; Quignon, Frédérique; Mouna, Lina; Poüs, Christian; Gruffat, Henri; Maréchal, Vincent; et al.
ABSTRACT: Mitochondria respond to many cellular functions and act as central hubs in innate immunity against viruses. This response is notably due to their role in the activation of interferon (IFN) signaling pathways through the activity of MAVS (mitochondrial antiviral signaling protein) present at the mitochondrial surface. Here, we report that the BHRF1 protein, a BCL2 homolog encoded by Epstein-Barr virus (EBV), inhibits IFNB/IFN-β induction by targeting the mitochondria. Indeed, we have demonstrated that BHRF1 expression modifies mitochondrial dynamics and stimulates DNM1L/Drp1-mediated mitochondrial fission. Concomitantly, we have shown that BHRF1 is pro-autophagic because it stimulates the autophagic flux by interacting with BECN1/Beclin 1. In response to the BHRF1-induced mitochondrial fission and macroautophagy/autophagy stimulation, BHRF1 drives mitochondrial network reorganization to form juxtanuclear mitochondrial aggregates known as mito-aggresomes. Mitophagy is a cellular process, which can specifically sequester and degrade mitochondria. Our confocal studies uncovered that numerous mitochondria are present in autophagosomes and acidic compartments using BHRF1-expressing cells. Moreover, mito-aggresome formation allows the induction of mitophagy and the accumulation of PINK1 at the mitochondria. As BHRF1 modulates the mitochondrial fate, we explored the effect of BHRF1 on innate immunity and showed that BHRF1 expression could prevent IFNB induction. Indeed, BHRF1 inhibits the IFNB promoter activation and blocks the nuclear translocation of IRF3 (interferon regulatory factor 3). Thus, we concluded that BHRF1 can counteract innate immunity activation by inducing fission of the mitochondria to facilitate their sequestration in mitophagosomes for degradation. Abbreviations: 3-MA: 3-methyladenine; ACTB: actin beta; BCL2: BCL2 apoptosis regulator; CARD: caspase recruitment domain; CCCP: carbonyl cyanide 3-chlorophenylhydrazone; CI: compaction index; CQ: chloroquine; DAPI: 4ʹ, 6-diamidino-2-phenylindole, dihydrochloride; DDX58/RIG-I: DExD/H-box helicase 58; DNM1L/Drp1: dynamin 1 like; EBSS: Earle's balanced salt solution; EBV: Epstein-Barr virus; ER: endoplasmic reticulum; EV: empty vector; GFP: green fluorescent protein; HEK: human embryonic kidney; IFN: interferon; IgG: immunoglobulin G; IRF3: interferon regulatory factor 3; LDHA: lactate dehydrogenase A; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAVS: mitochondrial antiviral signaling protein; MMP: mitochondrial membrane potential; MOM: mitochondrial outer membrane; PINK1: PTEN induced kinase 1; RFP: red fluorescent protein; ROS: reactive oxygen species; SQSTM1/p62: sequestosome 1; STING1: stimulator of interferon response cGAMP interactor 1; TOMM20: translocase of outer mitochondrial membrane 20; VDAC: voltage dependent anion channel.